Pengaruh Penambahan Inhibitor Organik dari Ekstrak Batang Tahongai (Kleinhovia hospita Linn) terhadap Korosi Baja API 5L - Triana Yunita; Rizky Yoel; Asih Wentika Putri Kusuma; Sulistijono Sulistijono (Jurnal Metalurgi dan Material Indonesia, 2019)
This research will study about concentration and immersion time effect of corrosion rate inhibition by using Tahongai (Kleinhovia hospita Linn.) stem extract in a 3.5% NaCl environment. Tests conducted in this research were: the test of Fourier Transform Infrared (FTIR) Spectroscopy to know the functional groups and the compounds contained in the Tahongai (Kleinhovia hospita Linn.) stem and allegedly contains flavonoids from the obtained functional group, Open Circuit Potential (OCP) test to obtain the corrosion data and the lowest corrosion rate which is 6.29x10-4 mm/year obtained on the samples with the addition of 400 ppm 30 day immersion. Efficiency maximum inhibitor obtained on samples with the addition of an inhibitor of 400 ppm 30 day immersion is 88.9336%.